(untitled) (Revista INTEREDU11, 2021)
The purpose of this article is to problematize the figure of the Mapuche Williche teacher in relation to the historical and socio-political development of their communities and the colonial school. This work is hermeneutical, the body of data is conformed up of the primary information record collected during the thesis process and of documentation such as memorials and legislation that underlie the development of intercultural experiences. In this process the Mapuche Williche teacher is placed in the context of a school that, despite the 25 years since the legal mandate to implement a bilingual intercultural education system has been installed, has not overcome the colonial heritage. The teacher is a relevant actor in the intense political-epistemic disputes that confront pedagogical and ideological discourses that question, on the one hand, the presence and legitimacy of them and the knowledge that they incorpo-rate into the school curriculum. On the other hand, the discourses question the colonial act of the school and, conceive it, within the framework of intercultural experiences as decolonizing possibilities.